TINJAUAN YURIDIS WASIAT WAJIBAH TERHADAP ANAK ANGKAT DI DALAM KOMPILASI HUKUM ISLAM - Ferlinda Ayu Oktafila (Fakultas Hukum Universitas Stikubank, 2017)
In Indonesia, there has been no unification or no entity which regulates adoption. Fostering or adoption is still causing problems for communities and governments. Not only in terms of the appointment, but also the problem of the division of property of the adoptive parents. Based on this, the authors raised the title